Real-world long-term safety and effectiveness of turoctocog alfa in the treatment of haemophilia A in Japan: results from a multicentre, non-interventional, post-marketing study - Azusa Nagao; Ayumi Deguchi; Keiji Nogami (Hematology)
Objectives To assess the safety and effectiveness of turoctocog alfa in previously treated patients (PTPs) and previously untreated patients (PUPs) with haemophilia A in a real-world setting in Japan.Methods This multicentre, non-interventional, post-marketing study recruited patients with haemophilia A who initiated treatment with turoctocog alfa from 18 sites (08/2014-12/2018). The primary endpoint was adverse events (AEs) during the 2-year study period.Results The safety and effectiveness analysis set included 39 patients. In total, 13 (33.3%) patients reported ≥1 AE; incidence rate was 60.4 events/100 patient-years of exposure (PYE). Treatment was withdrawn in two cases: pruritus in a PTP and factor VIII inhibitor development in a PUP. Inhibitor development occurred in 2.6% of all patients, with an incidence rate of 3.8 events/100 PYE. The rate of inhibitor development was 0%, 25% and 20% in PTPs, PUPs and PUPs with severe type, respectively. The haemostatic success rate was 91.4% for 383 bleeding episodes and 85.7% for 14 surgeries. The negative binomial annualised bleeding rate for the prophylaxis regimen was 6.19 episodes/year (95% CI, 3.69–10.38). The mean (SD) total consumption of turoctocog alfa (n = 34; excluding FVIII inhibitors) was 5,382.6 (7,180.1) IU/kg/year/patient; consumption was 4,133.1 (1,452.4) IU/kg/year/patient for prophylaxis.Discussion The effectiveness and safety profiles were comparable to those observed in other turoctocog alfa trials; effectiveness analysis and consumption were not affected by treatment regimens.Conclusion Long-term use of turoctocog alfa therapy in clinical practice posed no newly identified safety issues and was effective for prophylaxis and treatment of bleeds in patients with haemophilia A in Japan.